2017
DOI: 10.1007/s40993-017-0086-6
|View full text |Cite
|
Sign up to set email alerts
|

Triangles with prime hypotenuse

Abstract: The sequence 3, 5, 9, 11, 15, 19, 21, 25, 29, 35, . . . consists of odd legs in right triangles with integer side lengths and prime hypotenuse. We show that the upper density of this sequence is zero, with logarithmic decay. The same estimate holds for the sequence of even legs in such triangles. We expect our upper bound, which involves the Erdős-Ford-Tenenbaum constant, to be sharp up to a double-logarithmic factor. We also provide a nontrivial lower bound. Our techniques involve sieve methods, the distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…(In fact, Ford [5] has further shown that if the implied constant O(1) is replaced with −3/2, the resulting expression has the same magnitude as M (N ).) A more recent appearance of η occurs in Chow and Pomerance [3], where the odd legs in integer-sided right triangles with prime hypotenuse are considered. (The present note uses some techniques from [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation

Symmetric primes revisited

Banks,
Pollack,
Pomerance
2019
Preprint
Self Cite
“…(In fact, Ford [5] has further shown that if the implied constant O(1) is replaced with −3/2, the resulting expression has the same magnitude as M (N ).) A more recent appearance of η occurs in Chow and Pomerance [3], where the odd legs in integer-sided right triangles with prime hypotenuse are considered. (The present note uses some techniques from [3].…”
Section: Introductionmentioning
confidence: 99%
“…A more recent appearance of η occurs in Chow and Pomerance [3], where the odd legs in integer-sided right triangles with prime hypotenuse are considered. (The present note uses some techniques from [3]. )…”
Section: Introductionmentioning
confidence: 99%

Symmetric primes revisited

Banks,
Pollack,
Pomerance
2019
Preprint
Self Cite